Cranial vault thickness in non-human primates: Allometric and geometric analyses of the vault and its component layers. Issue 101 (December 2016) - Copes, Lynn E.
Abstract: Extremely thick cranial vaults have been noted as a diagnostic characteristic of Homo erectus since the first fossil of the species was identified, but relatively little work has been done on elucidating its variation within extant non-human primates. Cranial vault thickness (CVT) is not a monolithic trait, and the relationship of its layers to other morphological variables is unknown. Total CVT and the thickness of the cortical and diploë layers individually, as well as the ratio between diploë and total thickness, were calculated from 258 female individuals from 47 species of non-human primate. Measures of CVT were then regressed onto measures of body, brain, vault, facial, and mandibular size as well as vault shape. Total frontal and parietal CVT scales with positive allometry or isometry with measures of size across a combined non-human primate sample, although some variation exists within each infraorder and when diploë thickness alone is compared to measures of size. CVT in this sample correlates weakly with cranial vault shape, but the relationship described here contradicts an earlier hypothesis that long, low vaults should be thicker than higher, globular vaults. This study provides new data on the variation of vault morphology among extant primates that may be used to inform future hypotheses for the cranial vault hypertrophy of H. erectus .